Предмет: Математика,
автор: yorkshirbessi
Помогите решить пожалуйста
Приложения:
Ответы
Автор ответа:
0
Ответ:
21
Пошаговое объяснение:
S = (v+3)*3 = (v-3)*4 => 3v+9 = 4v-12 => v = 21
Автор ответа:
0
Ответ:
21
Пошаговое объяснение:
S = (v+3)*3 = (v-3)*4 => 3v+9 = 4v-12 => v = 21
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: dfgbnmrghjytr
Предмет: Литература,
автор: seregakozlov2
Предмет: Информатика,
автор: ichik4anna
Предмет: Английский язык,
автор: Shooook4D